pembelajaran interaktif; kedisip Peningkiatan Kedisiplinan dan Partisipasi Aktif Siswa Melalui Pembelajran Interaktif di MTs Masra'atul Ulum: Peningkiatan Kedisiplinan dan Partisipasi Aktif Siswa Melalui Pembelajran Interaktif di MTs Masra'atul Ulum - Haris, M.Rif'i Darmawan (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the effectiveness of interactive learning in encouraging increased discipline and student activity at MTs Mazra'atul Ulum Paciran. The researcher used a descriptive qualitative approach, with data collection techniques in the form of observation, interviews, and documentation. The findings of the study indicate that the interactive learning approach is able to increase student involvement both emotionally, socially, and intellectually during the learning process. Students appear more enthusiastic, show a greater sense of responsibility, and have a higher motivation to learn. Support from the classroom environment—such as neat room layout, availability of reading corners, and displays of student work—also contribute to creating a positive learning atmosphere. However, limitations in technological facilities, especially the lack of devices such as projectors, are obstacles that need to be overcome immediately. Therefore, solid cooperation between teachers, schools, and students is an important key in ensuring the sustainability and effectiveness of the implementation of interactive learning as a whole.